Wilsonian visions : the Williamstown Institute of Politics and American internationalism after the First World War - McAllister, James, 1964- (Cornell University Press, 2021)
"This book delivers an account of the liberal internationalism of Harry Garfield and the Williamstown Institute of Politics"--